Long-term exposure to wind turbine noise and redemption of antihypertensive medication: A nationwide cohort study. (December 2018) - Poulsen, Aslak Harbo; Raaschou-Nielsen, Ole; Peña, Alfredo; Hahmann, Andrea N.; Nordsborg, Rikke Baastrup; Ketzel, Matthias; Brandt, Jørgen; Sørensen, Mette
Abstract: Noise from wind turbines (WTs) has been reported more annoying than traffic noise at similar levels, and concerns have been raised about whether WT noise (WTN) can increase risk for cardiovascular disease. We aimed to investigate if long-term exposure to WTN increases risk for hypertension, estimated as redemption of prescriptions for antihypertensive drugs. We identified all Danish dwellings within a radius of 20 WT heights from a WT and 25% randomly selected dwellings within 20–40 WT heights radius. Using data on WT type and hourly wind conditions at each WT, we estimated hourly outdoor (10–10, 000 Hz) and low frequency (LF: 10–160 Hz) indoor WTN for all dwellings, and aggregated it as long-term nighttime running means. From nationwide registries, we identified 535, 675 persons age 25–85 years living in these dwellings for >1 year from 1996 to 2013, of whom 83, 729 fulfilled our case definition of redeeming ≥2 prescriptions and ≥180 defined daily doses of antihypertensive drugs within a year. Data were analyzed using Poisson regression according to categories of WTN exposure and adjustment for individual and area-level covariates. We found no associations between 5-year mean exposure to WTN during night and redemption of antihypertensives, with hazard ratios (HR) of 0.91 (95% confidence intervals (CI): 0.78–1.06) for outdoor WTN ≥ 42 dB(A) and of 1.06 (CI: 0.83–1.35) for indoor LF WTN ≥ 15 dB(A) when compared to the reference WTN levels (<24 dB(A) and <5 dB(A), respectively). The lack of association was consistent across sub-populations of people living on farms, far from major roads and with high validity of the noise estimate. For people younger than 65 years we found HRs of 0.81 (95% CI: 0.67–0.98) and 0.94 (95% CI: 0.68–1.30) for outdoor WTN ≥ 42 dB(A) and indoor WTN ≥ 15 dB(A), respectively, whereas for people above 65 years the corresponding HRs were 1.17 (95% CI: 0.90–1.52) and 1.28 (95% CI: 0.87–1.88). In conclusion, the present study does not support an association between WTN and redemption of antihypertensive medication. Highlights: We identified all Danes exposed to wind turbine noise (WTN) from 1982 to 2013. Outdoor and indoor low frequency WTN were modelled as 1- and 5-year running means. At start of follow-up, 7650 persons were exposed to ≥36 dB(A) outdoor WTN and 4081 persons to ≥10 dB indoor WTN. People redeeming anti-hypertensive medication (AHT) were identified from a register. We found no overall association between WTN and redemption of AHT.